2020
DOI: 10.1177/0004867420963744
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of depressed bipolar patients with current suicidal ideation

Abstract: Objective: Bipolar disorder is one of the most frequent psychiatric disorders among suicidal patients. A large part of patients with bipolar disorder (30–50%) will attempt suicide. Suicidal ideation being a major risk factor of suicidal act, it is crucial to better characterize patients with suicidal bipolar depression (i.e. depression with current suicidal ideation). The aim of this study was to characterize suicidal bipolar depressed patients in comparison with non-suicidal depressed patients in terms of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…Indeed, patients with suicidal depression have more severe baseline clinical features, respond less well to antidepressants, may have a different clinical course (e.g., depression remission) and have higher suicidal risk than depressed patients without SI [21][22][23][24][25]. We previously reported similar results in a study on two large cohorts of outpatients with unipolar depression [24].…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Indeed, patients with suicidal depression have more severe baseline clinical features, respond less well to antidepressants, may have a different clinical course (e.g., depression remission) and have higher suicidal risk than depressed patients without SI [21][22][23][24][25]. We previously reported similar results in a study on two large cohorts of outpatients with unipolar depression [24].…”
Section: Introductionsupporting
confidence: 55%
“…Thus, SI presence was defined by a score ≥ 2 for the suicide item of the IDSC30 (IDSC30-SI), the QIDS (QIDS-SI), or the BDI (BDI-SI). This BDI-SI cut-off was previously used [23] and is associated with a 7-fold higher risk of future death by suicide [57].…”
Section: Definition Of Suicidal Depressionmentioning
confidence: 99%
“…Another study showed that depressive symptomatology and its course were significantly different in suicidal and non-suicidal depressed patients (van Ballegooijen et al, 2019). About 20% of patients present persistent SI despite the improvement or remission of depression (Batterham et al, 2019; Nobile et al 2021; Seo et al, 2014). Finally, growing evidence suggests SB has its own physiopathology (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The Quick Inventory of Depressive Symptoms (QIDS) scale, without the item on suicidal ideation, was used to assess the depression level. Suicidal ideation was self-evaluated with item 12 of the QIDS, as conducted in previous studies [42]. The anxious state was self-evaluated with the Spielberg Anxiety Inventory (STAI).…”
Section: Affective Statesmentioning
confidence: 99%